2020
DOI: 10.3390/jcm9040960
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Neurophysiological Correlates of Emotion and Food Craving Regulation in Patients with Anorexia Nervosa

Abstract: Background: Difficulties in emotion regulation and craving regulation have been linked to eating symptomatology in patients with anorexia nervosa (AN), contributing to the maintenance of their eating disorder. Methods: To investigate clinical and electrophysiological correlates of these processes, 20 patients with AN and 20 healthy controls (HC) completed a computerized task during EEG recording, where they were instructed to down-regulate negative emotions or food craving. Participants also completed self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 86 publications
3
12
0
Order By: Relevance
“…Indeed, people with AN-R seem not to be addicted to food but quite the opposite, i.e., addicted to food deprivation, and they show real determination instead of losing control. In their recent paper, Mallorquí-Bagué et al (2020) concluded that patients with AN exhibited a successful down-regulation of food craving, despite the presence of food addiction symptomatology [63]. In the present study, we found a prevalence of FA in patients with AN-R that was far more substantial than in nonclinical samples (0 to 25%) [11].…”
Section: Resultssupporting
confidence: 52%
“…Indeed, people with AN-R seem not to be addicted to food but quite the opposite, i.e., addicted to food deprivation, and they show real determination instead of losing control. In their recent paper, Mallorquí-Bagué et al (2020) concluded that patients with AN exhibited a successful down-regulation of food craving, despite the presence of food addiction symptomatology [63]. In the present study, we found a prevalence of FA in patients with AN-R that was far more substantial than in nonclinical samples (0 to 25%) [11].…”
Section: Resultssupporting
confidence: 52%
“…Hypothesis testing studies analyze the empirical evidence obtained in a specific sample with different purposes: (a) to identify risk factors and underlying mechanisms that enable a better understanding of the etiology and the phenotypes of disorders [e.g. the study by Mallorquí‐Bagué and colleagues aiming at investigating clinical and electrophysiological correlates of emotion regulation and craving regulation in anorexia nervosa (AN) (Mallorquí‐Bagué et al, 2020)]; (b) to assess the therapeutic efficacy of treatments [such as the study by Fernández‐Aranda and colleagues analyzing the benefits of a serious video game (SVG) as a complementary program to enhance the general functioning of patients with BN (Fernandez‐Aranda et al, 2015)]; and (c) to find out the evolution over time of different disorders and their possible correlated factors [such as the work by Svedlund and colleagues, which assessed whether the efficiency of a medium‐term intervention in women with ED may be due to attention deficit hyperactivity disorder symptoms (Svedlund, Norring, Ginsberg, & von Hausswolff‐Juhlin, 2018), or the randomized clinical trial (RCT) by Loeb et al aimed at assessing the efficacy of family‐based treatment for paediatric obesity (FBT‐PO), when compared with nutrition education counselling for weight management (Loeb et al, 2019), or the study by Giombini and colleagues analyzing the benefits of using individual cognitive remediation therapy in inpatient setting with Anorexia nervosa (Giombini et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To address this important health issue, the current Special Issue collected 21 articles examining the most recent and relevant scientific findings regarding advances in ED. The published articles comprised three reviews and 18 research articles focusing on different aspects, such as genetic [ 7 ] and epigenetic factors [ 8 ], biomarkers [ 9 ], comorbidity [ 10 , 11 , 12 , 13 , 14 ], clinical phenotypes [ 15 , 16 ], neurocognition [ 12 , 17 , 18 , 19 , 20 , 21 ], treatment predictors [ 22 ], and treatment models and therapeutic targets [ 19 , 23 , 24 , 25 , 26 , 27 ]. Altogether, these studies may provide increased knowledge about the pathogenesis, the risk factors, the maintenance factors, and the most appropriate treatments tools for ED.…”
mentioning
confidence: 99%
“…This collection also includes a set of studies that analyze the role of implicit–explicit emotion in patients with ED and their families, supporting the important role of the emotion recognition [ 13 , 14 ], the expressed emotion [ 27 ] or the emotion regulation strategies [ 12 , 17 ] in the development and maintenance of these disorders.…”
mentioning
confidence: 99%
See 1 more Smart Citation